PERAN KELOMPOK TANI TERHADAP ANGGOTA KELOMPOK TANI KELELONDEI INDAH DI DESA AMPRENG KECAMATAN LANGOWAN BARAT - Romario Hevrain Palar; Charles Reijaaldo Ngangi; Benu Olfie Liesje Susana (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the role of farmer groups on members of the Kelelondei Indah Farmers Group in Ampreng Village, Langowan Barat District, Minahasa Regency. This research was conducted for 3 months from October to December 2018. The data used in this study were primary and secondary data. Primary data collection through direct interviews to 20 respondents based on questionnaires that have been prepared previously. Secondary data was obtained from the Ampreng Village office and from google searching to get relevant theses. The results showed that the role of farmer groups on members of the Kelelondei Indah Farmers Group was generally good because of the 9 roles there were 7 roles categorized as good. They are increasing productivity to increase income, developing self-sufficiency in farming, teaching and learning containers for members, cooperating in facing threats among fellow farmers, achieving economies of scale together in terms of quality, a place to strengthen farmer cooperation, develop farming business carried out by members of farmer groups. While there are 2 roles categorized as not good, namely a place to strengthen cooperation between farmer groups and other parties, and develop farming business which is carried out together as a group business entity. *eprm*